Temperature preference of juvenile lumpfish (Cyclopterus lumpus) originating from the southern and northern parts of Norway. (April 2020) - Mortensen, Atle; Johansen, Richard B.; Hansen, Øyvind J.; Puvanendran, Velmurugu
Abstract: Fish are ectothermic animals and have body temperatures close to that of the water they inhabit. They can still control their body temperatures by selecting habitats with temperatures that maximize their growth, feed conversion and wellbeing. Lumpfish, Cyclopterus lumpus, is widely distributed in the North Atlantic Ocean and therefore exposed to variable water temperatures. Lumpfish is extensively used as cleanerfish in salmon farming in Norway and exposed to a wide temperature range along the north-south axis of the Norwegian coastline. But, if these temperature ranges correspond to the preference temperatures of lumpfish is not known. If lumpfish has adapted to regional temperatures along the Norwegian coast, differences in preference temperature for fish from different regions should be evident. In a selective breeding perspective, different selection lines for preference temperature would then be useful for further development of lumpfish as a cleanerfish. We subjected lumpfish juveniles weighing 154–426g originated from northern (Group North – GN) and southern (Group South – GS) Norway to a temperature preference test, using an electronic shuttle box system. The system allowed the fish to control the water temperature by moving between two chambers, and thereby choosing its preferred temperature in the range from 5 to 16 °C. We started the temperature at 7.8 ± 1.37 °C for GN and 7.58 ± 1.34 °C for GS, but all the fish except four (two each from GN and GS) chose lower temperatures (5.03–7.6 °C) in the first 18 h and stayed closer to that temperature during the next 30 h. Based on the results, GN and GS lumpfish preferred 6.92 ± 1.8 and 6.2 ± 1.2, respectively, and there was no significant difference between the groups. Neither was there any significant difference in growth rates (SGR) between the two groups. Based on our results, we suggest that lumpfish from any geographical origin along the Norwegian coast can be used anywhere in Norway. It follows that lumpfish from a single selection line could be used at any salmon farm in Norway independent of its location. Highlights: First study to investigate the temperature preference of lumpfish. Temperature preference of lumpfish between 150 and 450 g is between 6 and 7 °C. Temperature preference is well below than the lumpfish rearing temperature (10 °C) used in land facilities. No differences in temperature preference of lumpfish regardless of the north and south origin. No need for separate breeding lines in breeding programs to account for differences in environmental temperature.